2020
DOI: 10.1016/j.compag.2019.105117
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised image translation using adversarial networks for improved plant disease recognition

Abstract: Acquisition of data in task-specific applications of machine learning like plant disease recognition is a costly endeavor owing to the requirements of professional human diligence and time constraints. In this paper, we present a simple pipeline that uses GANs in an unsupervised image translation environment to improve learning with respect to the data distribution in a plant disease dataset, reducing the partiality introduced by acute class imbalance and hence shifting the classification decision boundary tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(83 citation statements)
references
References 43 publications
0
74
0
Order By: Relevance
“…For example, metric learning could be used to learn similar features between a pair of images, thus enhancing the discriminative power of deep CNNs 37 . Alternatively, generative adversarial networks 38 may help improve error rates for poorly sampled species and low accuracy due to class imbalance by generating synthetic image data when new images are difficult to acquire.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metric learning could be used to learn similar features between a pair of images, thus enhancing the discriminative power of deep CNNs 37 . Alternatively, generative adversarial networks 38 may help improve error rates for poorly sampled species and low accuracy due to class imbalance by generating synthetic image data when new images are difficult to acquire.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with studies in the first phase, the two pioneering studies demonstrated the importance of understanding the mechanism of CNNs for stress phenotyping as well as the potential for stress severity quantification. Image annotation is still recognized as a limiting factor for using many DL algorithms (especially supervised ones), so researchers investigated the use of generative adversarial networks (GANs) to generate synthetic images for training CNN models for plant stress detection and classification [ 54 ]. AR-GAN based on Cycle-GAN was developed to translate contextual information learned between different image sets.…”
Section: Cnn-based Analytical Approaches For Image-based Plant Phementioning
confidence: 99%
“…Autoregressive Deep Convolutional Generative Adversarial Network (AR-GAN) [ 130 ] is an approach based on three optimisation functions: the standard GAN, cycle self-consistency, and, to increase the affinity between generated and original images in terms of quality, reconstruction activation [ 131 , 132 ]. The created dataset has been shown to enhance classification by +5.2%.…”
Section: Data Augmentationmentioning
confidence: 99%
“…It is important to note that there are both quantitative and qualitative methods of evaluation for GANs. Average precision is based upon a comparison between the label maps of generated and the real images using semantic segmentation metrics (intersection-over-union per pixel/class).The Fréchet inception distance tool measures the covariance of feature distributions in the real/generated data [ 133 ]; the computational efficiency of this method has also been proven for large-scale datasets [ 130 ]. Precision measures the quality of created images compared to the corresponding learned dataset, while recall measures the diversity of the generated data [ 133 ].…”
Section: Data Augmentationmentioning
confidence: 99%